Additive manufacturing (3D Printing)-applied construction: Smart node system for an irregular building façade - Na, Sangho; Kim, Sungjin; Moon, Sungkon (Journal of Building Engineering, 2022)
This paper presents a proposed node system for an actual building project, named the Galleria Department Store (GDS). The exterior of the building was designed as an irregular shape of curtain wall, and it had a challenge that the existing methods could not address the requirement. The GDS curtain wall comprises different flat glass shapes connected by varying deflection angles. This structural requirement caused unprecedented challenges, such as the vertex deflection phenomenon. The proposed method, named the Smart Node system, was developed and applied to the GDS project to address this challenge. Additive manufacturing (AM) technology was used in production, showing a novel method for irregular façade construction. The originality of this study is to accomplish a new construction method using the AM technology, and also it covers the quantified effect of this application. One of the key achievements is that the developed Smart Note system performed with 99.4% construction accuracy, where only 10 out of 1652 glass sheets required reworks or corrections. In addition, the analysis found that the length of the vertical span was identified as one of the most critical factors to prevent construction error(s). When the length of the section is less than 9.8 m, no construction issues were observed. The main contribution of this study lies in the accuracy level of construction delivery, which is 647 node and 1632 glass panel productions and installations. The novelty of this study also includes the qualitative description of practical trials and errors from carrying out an AM-applied construction of GDS's exterior façade.
Keywords: 3-D printing; 3D-printing; Additive manufacturing technology; Building facades; Curtain-walls; Irregular buildings; Irregular facade; Node system; Off-site construction; Smart nodes; 3D printing; Additive manufacturing; Irregular façade; Node system; Offsite construction